Children emotional and behavioural problems and its association with maternal depression in Jimma town, southwest Ethiopia. Issue 4 (2nd July 2020) - Alenko, Arefayne; Girma, Shimelis; Abera, Mubarek; Workicho, Abdulhalik
Abstract : Background: In sub-Saharan countries, one in five children and one in three women experiences emotional and behavioural problems (EBPs) and depression, respectively. While various factors were reported to affect the mental health of children, little is known about the impact of maternal depression on the offspring. Moreover, the magnitude of children's EBPs is barely known in Ethiopia. Aim: To determine the magnitude of child EBPs and its association with maternal depression in Jimma town, southwest Ethiopia. Methods: A quantitative cross-sectional study was conducted among 734 mother–child pairs in Jimma town from January to June, 2019. EBP was assessed by using the parent version of Strengths and Difficulties Questionnaire (SDQ) with cut-off score of ≥14. Maternal depression was assessed using Patient Health Questionnaire-9 with a cut-off score of ≥10. Data were entered into Epidata V.3.1 and exported to SPSS V.24 for analysis. Multivariable logistic regression was fitted to identify the strength of association between exposure and outcome variables. Results: Of the 734 participants, 146 (19.9%, 95% CI: 16.9% to 22.9%) met EBP criteria based on parent version of SDQ. Maternal depression had significant association with child EBP (adjusted OR=2.38, 95% CI: 1.55 to 3.66). In addition, children aged 7–10 years, family size categories of ≤3 and 4–6, maternal intimate partner violence and maternal khat use had significant association with child EBP. Conclusions and recommendations: A significant number of children suffer from EBP in Jimma town. Maternal depression is found to be a predictor of children's EBPs. Thus, there is a need to design and implement an integrated maternal and child mental health programme. The maternal and child health section at the national level should integrate and cascade routine maternal and child mental health screening and intervention modalities down to the family healthcare system.